Recurrent Keratocyst: Clinical experience applying diverse treatment methods. Two Case reports - Castillo Canseco, Hernan (2023)
The odontogenic keratocyst is an intraosseous lesion that arises from remains of the dental lamina and basal cells of the overlying mucosa. It occurs most frequently between the second and third decade of life, with an incidence between 5 to 14% of all odontogenic cysts; its recurrence varies according to the treatment, reaching 23% only with enucleation. The aim of this article is to report two cases of keratocyst with different treatment therapies in recurrent keratocyst (marsupialization, decompression and use of 5-fluoruracil); we disclose this report due to the importance of non-invasive treatments with adjuvant therapies that reduce recurrence in patients with keratocyst.